Quality of service and water safety of the consumers of Metropolitan Lima - Perú - Herrera Cometivos, Jhamely (2023)
The water situation for the families of metropolitan Lima is critical; As a result of global warming, the loss of water is accelerated and they do not have their own sources to provide users with this vital liquid element through the Sanitation Services Provider Entity (EPS) and they are indifferent to this reality, which reflects social exclusion and puts public health at risk, it is important to promote a culture of caring for water and generate social awareness. The objective of the study was to analyze previous research on the variables; quality of service and water security. The research methodology was descriptive. According to the bibliographic review, it is concluded that there is water insecurity and a low quality of the service provided, reducing the gap in access to drinking water, particularly for the most vulnerable population. The authorities must focus efforts on actions that contribute to the security and development of the population.